Woody species diversity, population structure, and regeneration status in the Gra-Kahsu natural vegetation, southern Tigray of Ethiopia - Atsbha, Tesfay (Heliyon, 2019)
The study was conducted at Gra-Kahsu protected natural vegetation (PNV) and communal grazing land (CGL), in order to evaluate the conservation impact level. The diversity of plant species, population structure of woody species, and regeneration status were analysed from 62 quadrats, each with 20 m × 20 m for trees and 5 m × 5 m for shrubs, using systematic sampling methods. A total of 64 vascular plant species belonging to 52 genera and 37 families from PNV and 43 plant species belonging to 34 genera and 25 families from CGL was identified. Shannon diversity index values of PNV and CGL were 2.29 and 1.84, respectively. The mean basal area of PNV and CGL were 8.29 and 5.32 m(2)/ha, respectively. Three community types from PNV and two from CGL were identified. The population structure of woody species based on diameter and height class distribution showed reflected reversed J-shape for PNV however, bell-shaped, and interrupted inverted J-shape for CGL. The regeneration status of PNV and CGL were considered as good (sapling > seedling > matures) and fair (mature > sapling > seedling), respectively. Therefore, the floristic analysis of these two adjacent land use systems located in similar landscape showed distinctive variation in floristic composition, diversity, and regeneration status, which could be taken as the best practice of restoration and rehabilitation programs like, area exclosure.